2022
DOI: 10.1002/anie.202209645
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Doping Effect on Two‐Photon Absorption and Luminescence of Atomically Precise Silver Ligated Nanoclusters

Abstract: Noble metal nanoclusters allow for the atomically-precise control of their composition. However, to create nanoclusters with pre-defined optical properties, comprehensive description of their structure-property relation is required. Here, we report the gold atom doping impact on one-photon and two-photon absorption (TPA) and luminescence properties of ligated silver nanoclusters via combined experimental studies and time-dependent density functional theory simulations (TD-DFT). We synthesized a series of Ag 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 49 publications
2
34
0
Order By: Relevance
“…9 Other factors like relativistic effects (mainly due to the Au atoms), the exact position of metal dopants, and heteronuclear Au−Ag bonds 10 can affect the fluorescence intensity of gold-doped nanoclusters. 11 While most of doping of nanoclusters with heteroatoms was done with the highly stable single thiolated (SR) Au 25 SR 18 , 12−18 and Ag 25 SR 18 , 19,20 dithiolated (SSR) Ag 29 SSR 12 nanoclusters 21−26 are another interesting candidate for doping strategies. 11 The use of dithiolated molecules allows for exploring different staple motifs (as compared to those obtained with single thiolated molecules) and therefore adds some versatility to doping strategies.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…9 Other factors like relativistic effects (mainly due to the Au atoms), the exact position of metal dopants, and heteronuclear Au−Ag bonds 10 can affect the fluorescence intensity of gold-doped nanoclusters. 11 While most of doping of nanoclusters with heteroatoms was done with the highly stable single thiolated (SR) Au 25 SR 18 , 12−18 and Ag 25 SR 18 , 19,20 dithiolated (SSR) Ag 29 SSR 12 nanoclusters 21−26 are another interesting candidate for doping strategies. 11 The use of dithiolated molecules allows for exploring different staple motifs (as compared to those obtained with single thiolated molecules) and therefore adds some versatility to doping strategies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For Ag 24 Au 1 DMBT 18 , it was demonstrated that the presence of the central Au dopant strongly influences linear and nonlinear optical properties, increasing PL upon both one-and twophoton excitations, with respect to undoped silver nanoclusters. 20 Indeed, the central silver atom replacement with Au atoms leads to the localization of electron charge in the icosahedral center, inducing changes in the electronic structure of Ag 24 Au 1 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Unlike large nanoparticles, metal nanoclusters exhibit strong quantum-size effects; that is, changing one atom in a nanocluster will introduce non-negligible disturbances in its electronic structure, drastically affecting its catalytic and optical performance. [14][15][16][17][18][19][20][21][22] These properties of metal nanoclusters provide a fascinating opportunity to study their structure-property relationship at the atomic level.…”
Section: Introductionmentioning
confidence: 99%